Family Therapy Interventions For Grief, Psychosis, And Divorce Testing The Effectiveness Of Scvet - Yacoub, Nisreen (مجلة دراسات في سيكولوجية الانحراف, 2024)
This study examined the impact of SCVET on 202 participants facing diverse family challenges: 101 participants in experimental group 1-coping with bereavement 10 males 15 females, 2-navigating divorce conflict 12 males 24 females or 3-supporting a family member with psychosis 24 males 16 females. Therapy took six-month period. The participants completed the FACES assessment before and after therapy. 101 participants were taken as controlled group suffering from same family problems underwent assessments without receiving intervention. T-test results showed significant differences in all FACES dimensions. Most clients from experimental groups had positive scores increased in Cohesion, Adaptability, Communication and Satisfaction. Clear decreasing in the negative dimensions was shown in data analysis such Not close-knit or connected, Intertwined and integrated, Rigid and Chaotic after sessions compared to pre sessions assessment on the FACES assessment scale. Also looking at percentages: The psychosis group experienced the highest overall improvement (172%), followed by the divorced group (56%), and the grieving group (33%). Psychosis group: Pre-therapy scores in the FACES assessment were indicative of disconnection and rigidity. Post-therapy, they became more connected and integrated. However, they also showed a decrease in negative scores (-37%). Grieving group: Improvement in overall scores (+33%) but a decrease in negative scores (-51%). This suggests they felt better overall but remained burdened by grief. Divorced group: Moderate improvement in overall scores (+56%) with a decrease in negative scores (-44%). They seem to have made progress in adjusting to post-divorce life. SCVET is a promising approach for families in Arabic culture.